2023
DOI: 10.3390/healthcare11081201
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aerobic Exercise on Variation of Oxidative Stress, hs-CRP and Cortisol Induced by Sleep Deficiency

Abstract: The aim of this study was to investigate the impact of sleep deficiency (SD) on oxidative stress, hs-CRP and cortisol levels and to examine the effects of different intensities of aerobic exercise on these parameters under SD conditions. Thirty-two healthy male university students participated in the study and underwent both normal sleep (NS, 8 h of sleep per night for 3 consecutive days) and SD (4 h of sleep per night for 3 consecutive days). After the SD period, the participants performed treatment for 30 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
0
0
Order By: Relevance
“…Another study investigated the impact of sleep deficiency on oxidative stress, PCR-us, and cortisol levels associated with different intensities of aerobic exercise. Exercises of varying intensities were compared, and the results suggested that lower exercise intensity was more effective in mitigating the negative effects of sleep deficiency [15].…”
mentioning
confidence: 99%
“…Another study investigated the impact of sleep deficiency on oxidative stress, PCR-us, and cortisol levels associated with different intensities of aerobic exercise. Exercises of varying intensities were compared, and the results suggested that lower exercise intensity was more effective in mitigating the negative effects of sleep deficiency [15].…”
mentioning
confidence: 99%